Optimized design and mechanical properties of TPMS porous structures based on selective laser sintering - Fan, Heng Liang; Abdullah, Yassin; Khairul Fikri, Tamrin; Sinin, Hamdan; Chao, Wang (SciELO - Scientific Electronic Library Online, 2024)
Triply periodic minimal surface (TPMS) structures are commonly used for lightweight and energy-absorption applications. TPMS structures have a high porosity and are prone to the pinch-off phenomenon. In this study, we designed primitive and Schoen I-graph-wrapped package (I-WP) structures with different porosities. An optimized design function was introduced to obtain a high-porosity P-I structure, which was less prone to pinch off. The mechanical properties of the structures with different porosities achieved using selective laser sintering technology were investigated. Results showed that the porosities of primitive, I-WP, and P-I structures exhibited different correlations with the constant t. The elastic modulus and yield strength of all three structures decreased with porosity. For the same porosity, the compressive strength and elastic modulus of the P-I porous structure exceeded those of the primitive and I-WP porous structures. Additionally, the primitive porous structure was predominantly in the stretching deformation mode, whereas the I-WP and P-I structures were mostly in the stretching and bending deformation modes. The P-I porous structure showed better energy-absorption properties than the primitive and I-WP structures. This study enriched extremely small-surface porous structures and provided a relevant basis for their application in engineering fields.